Acetylene hydrochlorination using Au/carbon: a journey towards single site catalysis. Issue 86 (4th October 2017) - Malta, Grazia; Freakley, Simon J.; Kondrat, Simon A.; Hutchings, Graham J.
Abstract : The replacement of mercuric chloride in the production of vinyl chloride monomer, a precursor to PVC, would greatly reduce the environmental impact of this large scale industrial process. Abstract : The replacement of mercuric chloride in the production of vinyl chloride monomer, a precursor to PVC, would greatly reduce the environmental impact of this large scale industrial process. The validation of single Au cations supported on carbon as the best catalyst for this reaction at an industrial scale has resulted from nearly 35 years of research. In this feature article we review the development of this catalyst system and address the limitations of a range of characterisation techniques used previously which may induce damage to the fresh catalyst. Following our latest findings using X-ray absorption spectroscopy, we show that under operating conditions the catalyst is atomically dispersed and can be classed as a single site catalyst, we give a perspective on future directions in single atom catalysis.